Acute Herpes Simplex Viral Esophagitis Occurring in 5 Immunocompetent Individuals With Eosinophilic Esophagitis. Issue 3 (April 2016) - Zimmermann, Dorothee; Criblez, Dominique H.; Dellon, Evan S.; Bussmann, Christian; Pfeifer, David; Froh, Matthias; Straumann, Alex
Abstract : N/A: Herpes simplex esophagitis (HSE) is an acute, severe viral infection of the esophagus, rarely occurring in immunocompetent individuals. Eosinophilic esophagitis (EoE) is a rare immune‐mediated esophageal disorder. We recently observed 5 severe HSE cases in diagnosed EoE patients. Four of the 5 patients had active, untreated EoE at the time of infection, so HSE is not likely a side effect of swallowed topical corticosteroids, the first‐line medical treatment of EoE. However, this coincidence of these 2 rare conditions raises the question of a causal relationship between these 2 forms of esophagitis, and whether active EoE might predispose to HSE infection.